Fire & blood - Martin, George R. R. (Martin, George R. R. Song of ice and fire., 2020)
Centuries before the events of A Game of Thrones, House Targaryen<U+2014>the only family of dragonlords to survive the Doom of Valyria<U+2014>took up residence on Dragonstone. Fire & Blood begins their tale with the legendary Aegon the Conqueror, creator of the Iron Throne, and goes on to recount the generations of Targaryens who fought to hold that iconic seat, all the way up to the civil war that nearly tore their dynasty apart. What really happened during the Dance of the Dragons? Why was it so deadly to visit Valyria after the Doom? What were Maegor the Cruel<U+2019>s worst crimes? What was it like in Westeros when dragons ruled the skies? These are but a few of the questions answered in this essential chronicle, as related by a learned maester of the Citadel and featuring more than eighty all-new black-and-white illustrations by artist Doug Wheatley<U+2014>including five all-new illustrations exclusive to this edition. Readers have glimpsed small parts of this narrative in such volumes as The World of Ice & Fire, but now, for the first time, the full tapestry of Targaryen history is revealed.